Biological Activities of Essential Oils from Leaves of Paramignya trimera (Oliv.) Guillaum and Limnocitrus littoralis (Miq.) Swingle - Nhan Trong Le; Duc Viet Ho; Tuan Quoc Doan; Anh Tuan Le; Ain Raal; Donatella Usai; Giuseppina Sanna; Antonio Carta; Paola Rappelli; Nicia Diaz; Piero Cappuccinelli; Stefania Zanetti; et al. (MDPI AG, 2020)
The present study aimed to determine the bioactivities of essential oils extracted from the leaves of Paramignya trimera and Limnocitrus littoralis, including cytotoxicity, antiviral, antibacterial, antimycotic, and antitrichomonas effects. Herein, it was indicated that P. trimera and L. littoralis oils showed no cytotoxicity on normal cells, namely MT-4, BHK-21, MDBK, and Vero-76. P. trimera oil (i) exhibited the strongest inhibition against Staphylococcus aureus with MIC and MLC values of 2% (v/v); (ii) showed MIC and MLC values of 8% (v/v) in Candida parapsilosis; and (iii) in the remaining strains, showed MIC and MLC values greater than or equal to 16% (v/v). On the other hand, L. littoralis oil (i) displayed the strongest inhibition against Candida tropicalis and Candida parapsilosis with 2% (v/v) of MIC and MLC; and (ii) in the remaining strains, possessed MIC and MLC greater than or equal to 16% (v/v). In addition, antitrichomonas activities of the oils were undertaken, showing IC50, IC90, MLC values, respectively, at 0.016%, 0.03%, and 0.06% (v/v) from P. trimera, and 0.03%, 0.06%, 0.12% (v/v) from L. littoralis, after 48 h of incubation. The oils were completely ineffective against ssRNA+ (HIV-1, YFV, BVDV, Sb-1, CV-B4), ssRNA- (RSV, VSV), dsRNA (Reo-1), and dsDNA (HSV-1, VV) viruses. This is the first report describing the cytotoxicity, antiviral, antibacterial, antimycotic, and antitrichomonas activities of the essential oils of P. trimera and L. littoralis.